Environment-friendly easy-to-tear adhesive tape and preparation method thereof
By applying special environmentally friendly adhesives to the plastic film, the problems of difficulty in tearing and harmful solvents in existing tapes are solved, and tapes with easy tear, high bond strength and good water resistance are achieved.
Patent Information
- Application Number
- CN202411602109.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-04
AI Technical Summary
The existing tape is difficult to tear off after bonding, and the organic solvents used are harmful to human health and have poor water resistance, which limits its scope of use.
The tear-tearing tape including a plastic film and an environmentally friendly adhesive bonded to one side of it is made of components such as acrylate, methacrylic acid, oxidized microcrystalline cellulose, etc., and is prepared by a specific preparation method.
It realizes the tearability and high bonding strength of the tape, and has good water resistance and environmental protection properties, avoiding the use of harmful solvents.
Smart Images

Figure CN119552589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesive tapes, and in particular to an environmentally friendly easy-tear adhesive tape and a preparation method thereof. Background Art
[0002] Adhesive tape can be seen everywhere in life and has a wide range of uses. It is currently widely used in packaging and sealing. Transparent tape is made by applying glue on the surface of the original BOPP film after high-voltage corona treatment to make one side rough. The tape has a good packaging effect, is non-toxic and odorless, and can also be used in packaging and some electronic industries, which is extremely convenient.
[0003] Existing tapes generally use organic acrylic adhesives as bonding materials, most of which are toluene or mixed solvent types. Although they have good bonding effects, organic solvents such as toluene are easily volatile and can be absorbed by the human body, endangering human health, which is not conducive to environmental protection and hygiene. At the same time, they have poor water resistance, which limits their use.
[0004] At present, it is difficult to open or tear off the adhesive product because the adhesive tape is very tightly bonded. In the prior art, the production process of easy-to-tear adhesive products is usually to improve the adhesive tape or label with stickiness on the whole surface so that a small part loses its stickiness, and its production process is very inconvenient.
[0005] At present, how to prepare an easy-to-tear adhesive tape that is safe, environmentally friendly, water-resistant, and has good bonding effect has become a technical problem that needs to be solved. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an environmentally friendly easy-tear adhesive tape and a preparation method thereof.
[0007] An environmentally friendly easy-tear tape comprises: a plastic film and an environmentally friendly adhesive attached to one side of the plastic film; wherein the width of the environmentally friendly adhesive is a , the plastic film width is b , a < b ; The environmentally friendly adhesive is located in the middle of the plastic film, and the distances between the two edges of the environmentally friendly adhesive and the two edges of the plastic film are equal.
[0008] Preferably, the raw materials of the environmentally friendly adhesive include, by mass: 30-70 parts of acrylate, 5-10 parts of methacrylic acid, 5-15 parts of oxidized microcrystalline cellulose, 1-2 parts of alkylphenol polyoxyethylene ether, 1.1-6 parts of sodium bicarbonate, 1-5 parts of amino polystyrene microspheres, 1-2 parts of graphene oxide, 1-2 parts of initiator, 1-2 parts of sodium dodecylbenzene sulfonate, and 1-2 parts of amino-terminated polyamidoamine.
[0009] Preferably, the acrylic acid ester is methyl methacrylate and / or butyl acrylate.
[0010] Preferably, the acrylic ester is composed of methyl methacrylate and butyl acrylate in a mass ratio of 20-50:10-20.
[0011] Preferably, the particle size of the amino polystyrene microspheres is 100-150 nm.
[0012] Preferably, the initiator is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.
[0013] Preferably, the generation number of the amino-terminated polyamidoamine is 2.0-4.0.
[0014] Preferably, the oxidized microcrystalline cellulose is obtained by oxidizing microcrystalline cellulose with 2,2,6,6-tetramethylpiperidinium oxide, sodium bromide and sodium hypochlorite, wherein a sodium carbonate / sodium bicarbonate buffer solution is used as the solvent.
[0015] Preferably, the environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide are added to water, stirred at 50-70°C for 1-2 hours, initiator, sodium dodecylbenzene sulfonate, sodium bicarbonate, and amino-terminated polyamidoamine are added, stirred at 40-50°C for 1-2 hours, and preform a is obtained; (2) Mix acrylate, methacrylic acid, oxidized microcrystalline cellulose, alkylphenol polyoxyethylene ether, sodium bicarbonate and water, and stir at 40-50° C. for 1-2 hours to obtain preform b; (3) While stirring, add preform b dropwise to preform a. Continue stirring for 1-2 hours after the addition is complete. Adjust the system temperature to 70-90°C, stir for 1-4 hours, cool to room temperature, adjust the system pH to 8-9, and stir for 1-2 hours.
[0016] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating an environmentally friendly adhesive on one side of a plastic film, plasticizing at 120-140° C. for 1-2 minutes, and rolling up.
[0017] Preferably, the coating amount of the environmentally friendly adhesive is 30-40g / m 2 . Beneficial Effects
[0018] The present invention can significantly improve the heat resistance stability of the product by firmly combining lamellar graphene oxide on the surface of polystyrene microspheres and modifying acrylic monomers. At the same time, the adhesive has barrier properties and excellent water-blocking effect. The microsphere structure is effectively combined with the polyacrylate continuous phase structure, which not only greatly improves the cohesive strength of the product, but also has excellent sustained adhesion performance. In combination with the dendritic polyamide amine structure, the activity of the polymer chain end is restricted. Although the initial adhesion performance is reduced, it is found through experiments that the peel strength is significantly improved, which can meet higher bonding strength requirements.
[0019] Oxidized microcrystalline cellulose not only has excellent uniformity in dispersion in methyl methacrylate, butyl acrylate, and methacrylic acid, but can also reduce the agglomeration of microcrystalline cellulose particles and improve the interfacial properties with acrylic resins. At the same time, it can combine with the active groups on terminal amino polyamide amine and graphene oxide to effectively form a continuous phase network structure with good compatibility, thereby effectively improving the bonding strength of the product.
[0020] The present invention applies an environmentally friendly adhesive on a plastic film, which can meet the bonding function and water resistance, and has excellent thermal stability. The easy-tear tape of the present invention is not only knife-free and easy to tear, but also has high bonding strength, greatly improves work efficiency, saves time and labor, and is non-toxic, odorless, and environmentally friendly. The present invention has extremely low VOC emissions when used, the product is green and environmentally friendly, and has higher safety in use. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figures are a comparison of the thermal decomposition temperatures of the environmentally friendly adhesives obtained in Example 5 and Comparative Examples 1-3, and a comparison of the water absorption rates of the environmentally friendly easy-tear tapes obtained in Example 5 and Comparative Examples 1-3.
[0022] Figure 2 The figure is a comparison chart of the initial adhesion and the sustained adhesion of the environmentally friendly easy-tear tapes obtained in Example 5 and Comparative Examples 1-3.
[0023] Figure 3 The following is a comparison chart of the 20-min and 24-h peeling adhesion of the environmentally friendly easy-tear tapes obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0024] The present invention will be further explained below in conjunction with specific embodiments.
[0025] The amino polystyrene microspheres used below were purchased from Shaanxi Xingbei Aike Biotechnology Co., Ltd., and the average particle size thereof was 120 nm. The OP-10 used below was purchased from Shandong Shangqiao New Materials Co., Ltd.
[0026] The oxidized microcrystalline cellulose used below was prepared by the following specific operation: 1.0 g of microcrystalline cellulose (6 mmol of glucose unit) was suspended in 75 mL of Na2CO3 / NaHCO3 buffer solution with a pH of 10.83, and stirred at high speed for 2 min; 30 mg of TEMPO (0.2 mmol) and 0.32 g of NaBr (3.1 mmol) were added, and the temperature was strictly controlled at 30°C. After TEMPO and NaBr were completely dissolved, 4.10 mL of 21% NaClO solution (13.20 mmol) was added four times every 30 min. The NaClO solution must be diluted with 0.5 M before being added to the reaction system. The pH of the HCl solution was adjusted to 10; when the reaction time reached 5h and the oxidation reaction was basically complete, the oxidation reaction was stopped, the reaction mixture was poured out, and centrifuged several times with a high-speed centrifuge until the upper reaction liquid was clear, and the supernatant was filtered out with a G5-grade sand core funnel, and the pH value of the supernatant was adjusted to 3, and 3 times the volume of ethanol was added to precipitate the oxidation product; the precipitated oxidation product was repeatedly washed with anhydrous ethanol and acetone several times, and dried in a vacuum drying oven at 40°C. Example
[0027] An environmentally friendly easy-tear tape comprises: a plastic film and an environmentally friendly adhesive attached to one side of a BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0028] Among them, the raw materials of the environmentally friendly adhesive include: 300g methyl methacrylate, 50g methacrylic acid, 50g oxidized microcrystalline cellulose, 10g OP-10, 11g sodium bicarbonate, 10g amino polystyrene microspheres, 10g graphene oxide, 10g potassium persulfate, 10g sodium dodecylbenzene sulfonate, and 10g 2.0 generation amino-terminated polyamidoamine.
[0029] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 200 g of water, stirred at 50 °C for 1 h, potassium persulfate, sodium dodecylbenzene sulfonate, 1 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 40 °C for 1 h to obtain preform a; (2) Methyl methacrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 10 g of sodium bicarbonate, and 1000 g of water were mixed and stirred at 40° C. for 1 h to obtain preform b; (3) While stirring, add preform b dropwise into preform a. Continue stirring for 1 h after the addition is complete. Adjust the system temperature to 70 °C, stir for 1 h, cool to room temperature, add ammonia water dropwise until the pH value of the system is 8-9, and stir for 1 h.
[0030] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 30 g / m 2 , plasticize at 120℃ for 1min and roll up. Example
[0031] An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0032] Among them, the raw materials of the environmentally friendly adhesive include: 700g butyl acrylate, 100g methacrylic acid, 150g oxidized microcrystalline cellulose, 20g OP-10, 60g sodium bicarbonate, 50g amino polystyrene microspheres, 20g graphene oxide, 20g sodium persulfate, 20g sodium dodecylbenzene sulfonate, and 20g 4.0 generation amino-terminated polyamidoamine.
[0033] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 400 g of water, stirred at 70 °C for 2 h, sodium persulfate, sodium dodecylbenzene sulfonate, 10 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 50 °C for 2 h to obtain preform a; (2) Butyl acrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 50 g of sodium bicarbonate, and 1500 g of water were mixed, and stirred at 50° C. for 2 h to obtain preform b; (3) While stirring, add preform b dropwise into preform a. Continue stirring for 2 h after the addition is complete. Adjust the system temperature to 90 °C and stir for 4 h. Cool the system temperature to room temperature and add ammonia water dropwise until the pH value of the system is 8-9. Continue stirring for 2 h.
[0034] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 40 g / m 2 , plasticize at 140℃ for 2min and roll up. Example
[0035] An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0036] Among them, the raw materials of the environmentally friendly adhesive include: 300g methyl methacrylate, 180g butyl acrylate, 70g methacrylic acid, 120g oxidized microcrystalline cellulose, 13g OP-10, 43g sodium bicarbonate, 40g amino polystyrene microspheres, 13g graphene oxide, 17g ammonium persulfate, 12g sodium dodecylbenzene sulfonate, and 13g 3.5-generation amino-terminated polyamidoamine.
[0037] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 350 g of water, stirred at 55 °C for 100 min, ammonium persulfate, sodium dodecylbenzene sulfonate, 3 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 48 °C for 80 min to obtain preform a; (2) Methyl methacrylate, butyl acrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 40 g of sodium bicarbonate, and 1100 g of water were mixed, and stirred at 47° C. for 80 min to obtain preform b; (3) While stirring, add preform b dropwise into preform a. After the addition is complete, continue stirring for 100 min. Adjust the system temperature to 75 °C and stir for 3 h. Cool the mixture to room temperature and add ammonia water dropwise until the pH value of the system reaches 8-9. Stir for 80 min.
[0038] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 33 g / m 2 , plasticize at 135℃ for 1.5min, and roll up. Example
[0039] An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0040] Among them, the raw materials of the environmentally friendly adhesive include: 400g methyl methacrylate, 120g butyl acrylate, 90g methacrylic acid, 80g oxidized microcrystalline cellulose, 17g OP-10, 27g sodium bicarbonate, 20g amino polystyrene microspheres, 17g graphene oxide, 13g ammonium persulfate, 18g sodium dodecylbenzene sulfonate, and 17g 2.5-generation amino-terminated polyamidoamine.
[0041] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 250 g of water, stirred at 65 °C for 80 min, ammonium persulfate, sodium dodecylbenzene sulfonate, 7 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 42 °C for 100 min to obtain preform a; (2) Methyl methacrylate, butyl acrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 20 g of sodium bicarbonate, and 1300 g of water were mixed and stirred at 43° C. for 100 min to obtain preform b; (3) While stirring, add preform b dropwise into preform a. After the addition is complete, continue stirring for 80 min. Adjust the system temperature to 85 °C and stir for 2 h. Cool the mixture to room temperature and add ammonia water dropwise until the pH value of the system reaches 8-9. Stir for 100 min.
[0042] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 37 g / m 2 , plasticize at 125℃ for 1.5min, and roll up. Example
[0043] An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0044] Among them, the raw materials of the environmentally friendly adhesive include: 350g methyl methacrylate, 150g butyl acrylate, 80g methacrylic acid, 100g oxidized microcrystalline cellulose, 15g OP-10, 35g sodium bicarbonate, 30g amino polystyrene microspheres, 15g graphene oxide, 15g ammonium persulfate, 15g sodium dodecylbenzene sulfonate, and 15g 3.0 generation amino-terminated polyamidoamine.
[0045] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 300 g of water, stirred at 60 °C for 90 min, and ammonium persulfate, sodium dodecylbenzene sulfonate, 5 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 45 °C for 90 min to obtain preform a; (2) Methyl methacrylate, butyl acrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 30 g of sodium bicarbonate, and 1200 g of water were mixed, and stirred at 45° C. for 90 min to obtain preform b; (3) While stirring, add preform b dropwise into preform a. After the addition is complete, continue stirring for 90 min. Adjust the system temperature to 80 °C and stir for 2.5 h. Cool the system temperature to room temperature and add ammonia water dropwise until the pH value of the system is 8-9. Stir for 90 min.
[0046] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 35 g / m 2 , plasticize at 130℃ for 1.5min, and roll up.
[0047] Comparative Example 1 An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0048] Among them, the raw materials of the environmentally friendly adhesive include: 350g methyl methacrylate, 150g butyl acrylate, 80g methacrylic acid, 100g microcrystalline cellulose, 15g OP-10, 35g sodium bicarbonate, 30g amino polystyrene microspheres, 15g graphene oxide, 15g ammonium persulfate, 15g sodium dodecylbenzene sulfonate, and 15g 3.0 generation amino-terminated polyamidoamine.
[0049] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 300 g of water, stirred at 60 °C for 90 min, and ammonium persulfate, sodium dodecylbenzene sulfonate, 5 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 45 °C for 90 min to obtain preform a; (2) Methyl methacrylate, butyl acrylate, methacrylic acid, microcrystalline cellulose, OP-10, 30 g of sodium bicarbonate, and 1200 g of water were mixed, and stirred at 45° C. for 90 min to obtain preform b; (3) While stirring, add preform b dropwise into preform a. After the addition is complete, continue stirring for 90 min. Adjust the system temperature to 80 °C and stir for 2.5 h. Cool the system temperature to room temperature and add ammonia water dropwise until the pH value of the system is 8-9. Stir for 90 min.
[0050] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 35 g / m 2 , plasticize at 130℃ for 1.5min, and roll up.
[0051] Comparative Example 2 An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0052] Among them, the raw materials of the environmentally friendly adhesive include: 350g methyl methacrylate, 150g butyl acrylate, 80g methacrylic acid, 100g oxidized microcrystalline cellulose, 15g OP-10, 35g sodium bicarbonate, 30g polystyrene microspheres, 15g graphene oxide, 15g ammonium persulfate, 15g sodium dodecylbenzene sulfonate, and 15g 3.0 generation amino-terminated polyamidoamine.
[0053] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, polystyrene microspheres and graphene oxide were added to 300 g of water, stirred at 60 °C for 90 min, ammonium persulfate, sodium dodecylbenzene sulfonate, 5 g of sodium bicarbonate, and amino-terminated polyamidoamine were added, and stirred at 45 °C for 90 min to obtain preform a; (2) Methyl methacrylate, butyl acrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 30 g of sodium bicarbonate, and 1200 g of water were mixed, and stirred at 45° C. for 90 min to obtain preform b; (3) While stirring, add preform b dropwise into preform a. After the addition is complete, continue stirring for 90 min. Adjust the system temperature to 80 °C and stir for 2.5 h. Cool the system temperature to room temperature and add ammonia water dropwise until the pH value of the system is 8-9. Stir for 90 min.
[0054] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 35 g / m 2 , plasticize at 130℃ for 1.5min, and roll up.
[0055] Comparative Example 3 An environmentally friendly easy-tear adhesive tape comprises: a BOPP film and an environmentally friendly adhesive attached to one side of the BOPP film; wherein the minimum distance between the two edges of the environmentally friendly adhesive and the two edges of the BOPP film is 1 cm.
[0056] Among them, the raw materials of the environmentally friendly adhesive include: 350g methyl methacrylate, 150g butyl acrylate, 80g methacrylic acid, 100g oxidized microcrystalline cellulose, 15g OP-10, 35g sodium bicarbonate, 30g amino polystyrene microspheres, 15g graphene oxide, 15g ammonium persulfate, 15g sodium dodecylbenzene sulfonate, and 15g 3.0 generation amino-terminated polyamidoamine.
[0057] The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide were added to 300 g of water, stirred at 60 °C for 90 min, ammonium persulfate, sodium dodecylbenzene sulfonate and 5 g of sodium bicarbonate were added, and stirred at 45 °C for 90 min to obtain preform a; (2) Methyl methacrylate, butyl acrylate, methacrylic acid, oxidized microcrystalline cellulose, OP-10, 30 g of sodium bicarbonate, and 1200 g of water were mixed, and stirred at 45° C. for 90 min to obtain preform b; (3) While stirring, add preform b dropwise into preform a. After the addition is complete, continue stirring for 90 min. Adjust the system temperature to 80 °C and stir for 2.5 h. Cool to room temperature and add ammonia water dropwise until the pH value of the system is 8-9. Add amino-terminated polyamide amine and stir for 90 min.
[0058] The preparation method of the above-mentioned environmentally friendly easy-tear tape comprises the following steps: coating the environmentally friendly adhesive on one side of the BOPP film with a coating amount of 35 g / m 2 , plasticize at 130℃ for 1.5min, and roll up.
[0059] The thermal decomposition temperature of the environmentally friendly adhesives obtained in Example 5 and Comparative Examples 1-3 was tested as follows: After drying each group of environmentally friendly adhesives to constant weight, thermogravimetric analysis was performed at a rate of 10°C / min in an air atmosphere, and the thermal decomposition temperature of the TG curve was calculated by the tangent method.
[0060] The environmentally friendly easy-tear tapes obtained in Example 5 and Comparative Examples 1-3 were pasted on a stainless steel plate with a flat surface and gently pressed with fingers; a standard test roller was rolled back and forth on each sample 5 times at a speed of about 10 mm / min to ensure that the sample was in full contact with the surface of the stainless steel plate. The samples were weighed after being placed for 24 hours, and then completely immersed in water for 48 hours. The samples were taken out, drained, weighed, and the water absorption rate was calculated.
[0061] like Figure 1 As shown, the thermal decomposition temperature of the environmentally friendly adhesive obtained in Example 5 is similar to that of Comparative Example 3 (P>0.05), and is better than that of Comparative Examples 1-2 (P<0.05); and the water absorption rate of the environmentally friendly easy-tear tape obtained in Example 5 is slightly better than that of Comparative Example 3, but there is no significant difference (P>0.05), and its water absorption rate is better than that of Comparative Examples 1-2 (P<0.05).
[0062] The initial adhesion of the environmentally friendly easy-tear tapes obtained in Example 5 and Comparative Examples 1-3 (wherein the width of the environmentally friendly adhesive is 25 mm and the length is 180 mm) was measured as follows: the two ends of each sample were glued together, with the side coated with the adhesive facing downward, and clamped in the upper clamping plate of a tensile testing machine; a stainless steel plate with a flat surface was fixed on the upper clamping plate, and then the upper clamping plate was lowered so that the adhesive tape and the template surface were completely in contact and then immediately separated (the separation speed was 300 mm / min).
[0063] The holding force of the environmentally friendly easy-tear tapes obtained in Example 5 and Comparative Examples 1-3 (wherein the width of the environmentally friendly adhesive is 25 mm and the length is 180 mm) was measured as follows: lines were drawn at 25 mm and 30 mm on one end of each sample, the unlined end of the sample was folded to 30 mm and fixed with a stapler, and the adhesive-coated side was placed downward on a glass sheet and gently pressed with fingers; a standard test roller was rolled back and forth on each sample 5 times at a speed of about 10 mm / min to ensure that the sample was in full contact with the surface of the glass sheet, and then left for 20 minutes before testing; a 1 kg weight was hung under the sample, and the time taken to fall was recorded.
[0064] like Figure 2 As shown, the initial adhesion of the environmentally friendly easy-tear tapes obtained in Example 5, Comparative Example 1 and Comparative Example 2 is lower than that in Comparative Example 3 (P < 0.05), and the initial adhesion of the environmentally friendly easy-tear tapes obtained in Example 5, Comparative Example 1 and Comparative Example 2 is similar, lacking significant difference (P > 0.05); the lasting adhesion of the environmentally friendly easy-tear tapes obtained in Example 5, Comparative Example 1 and Comparative Example 2 is higher than that in Comparative Example 3 (P < 0.05), and the lasting adhesion of the environmentally friendly easy-tear tape obtained in Example 5 is higher than that in Comparative Examples 1-2 (P < 0.05).
[0065] The peeling adhesion of the environmentally friendly easy-tear tape obtained in Example 5 and Comparative Examples 1-3 (wherein the width of the environmentally friendly adhesive is 25 mm and the length is 180 mm) was measured as follows: each group of samples was placed on a stainless steel plate with a flat surface with the adhesive side facing downward and lightly pressed with fingers; a standard test roller was rolled back and forth on each sample at a speed of about 10 mm / min for 5 times to make the sample completely contact with the surface of the stainless steel plate, and after being placed for 20 minutes, the sample and the stainless steel plate were fixed on the test machine so that the peeling angle was 180°; the separation speed of the test machine fixture was set to 5-500 mm / min, and a number was read every 10 mm in the middle of each sample during the test, and at least 5 numbers were read, and the average of the five numbers was the peeling force of the sample. The same method was used to test the sample and the stainless steel plate after being placed for 24 hours.
[0066] like Figure 3As shown, the 20-min peeling viscosity of the environmentally friendly easy-tear tape obtained in Example 5 is similar to that of Comparative Example 3 (P>0.05), and is better than Comparative Examples 1-2 (P<0.05); and the 24-h peeling viscosity of the environmentally friendly easy-tear tape obtained in Example 5 is the highest, which is better than Comparative Examples 1-3 (P<0.05).
[0067] The applicant believes that the reason for the above results is that: the present invention can significantly improve the heat resistance stability of the product by firmly combining lamellar graphene oxide on the surface of polystyrene microspheres and modifying acrylic monomers. At the same time, the adhesive has barrier properties and excellent water-blocking effect; at the same time, a bonding effect is generated in the polyacrylate system, and the bonding force is strong. The microsphere structure is effectively combined with the continuous phase structure, which not only greatly improves the cohesive strength of the product, but also has excellent sustained adhesion performance. In combination with the dendritic polyamide amine structure, the activity of the polymer chain end is restricted. Although the initial adhesion performance decreases, it is found through experiments that its peel strength is significantly improved, and a higher bonding strength requirement can be achieved. Oxidized microcrystalline cellulose not only has excellent uniformity of dispersion in methyl methacrylate, butyl acrylate, and methacrylic acid, can reduce the agglomeration of microcrystalline cellulose particles, and improve the interface performance with acrylic resin, but also can be combined with the active groups on the terminal amino polyamide amine and graphene oxide to effectively form a continuous phase network structure with good compatibility, effectively improving the bonding strength of the product.
[0068] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An environmentally friendly easy-tear tape, characterized in that: include: A plastic film and an environmentally friendly adhesive attached to one side of the plastic film, wherein the environmentally friendly adhesive is located in the middle of the plastic film; The width of the environmentally friendly adhesive is a , the plastic film width is b , a < b ; The raw materials of the environmentally friendly adhesive include, by mass, 30-70 parts of acrylate, 5-10 parts of methacrylic acid, 5-15 parts of oxidized microcrystalline cellulose, 1-2 parts of alkylphenol polyoxyethylene ether, 1.1-6 parts of sodium bicarbonate, 1-5 parts of amino polystyrene microspheres, 1-2 parts of graphene oxide, 1-2 parts of initiator, 1-2 parts of sodium dodecylbenzene sulfonate, and 1-2 parts of amino-terminated polyamidoamine.
2. The environmentally friendly easy-tear tape according to claim 1, characterized in that: The acrylic acid ester is methyl methacrylate and / or butyl acrylate.
3. The environmentally friendly easy-tear tape according to claim 1, characterized in that: The acrylic ester is composed of methyl methacrylate and butyl acrylate in a mass ratio of 20-50:10-20.
4. The environmentally friendly easy-tear tape according to claim 1, characterized in that: The particle size of amino polystyrene microspheres is 100-150 nm.
5. The environmentally friendly easy-tear tape according to claim 1, characterized in that: The initiator is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.
6. The environmentally friendly easy-tear tape according to claim 1, characterized in that: The generation number of the amino-terminated polyamidoamine is 2.0-4.
0.
7. The environmentally friendly easy-tear tape according to claim 1, characterized in that: Oxidized microcrystalline cellulose is obtained by oxidizing microcrystalline cellulose with 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite, wherein a sodium carbonate / sodium bicarbonate buffer solution is used as a solvent.
8. The environmentally friendly easy-tear tape according to claim 1, characterized in that: The environmentally friendly adhesive is prepared by the following specific steps: (1) Under nitrogen protection, amino polystyrene microspheres and graphene oxide are added to water, stirred at 50-70°C for 1-2 hours, initiator, sodium dodecylbenzene sulfonate, sodium bicarbonate, and amino-terminated polyamidoamine are added, stirred at 40-50°C for 1-2 hours, and preform a is obtained; (2) Mix acrylate, methacrylic acid, oxidized microcrystalline cellulose, alkylphenol polyoxyethylene ether, sodium bicarbonate and water, and stir at 40-50° C. for 1-2 hours to obtain preform b; (3) While stirring, add preform b dropwise to preform a. Continue stirring for 1-2 hours after the addition is complete. Adjust the system temperature to 70-90°C, stir for 1-4 hours, cool to room temperature, adjust the system pH to 8-9, and stir for 1-2 hours.
9. A method for preparing the environmentally friendly easy-tear tape according to any one of claims 1 to 8, characterized in that: The process includes the following steps: applying an environmentally friendly adhesive to one side of the plastic film at a coating amount of 30-40 g / m 2 , plasticize at 120-140℃ for 1-2min, and roll up.
10. The method for preparing the environmentally friendly easy-tear tape according to claim 9, characterized in that: The coating amount of environmentally friendly adhesive is 30-40g / m 2 .